Investigation of the influence of nano-sized particles on the entanglement distribution of a generic polymer nanocomposite using molecular dynamics - Seibert, Jakob; Pfaller, Sebastian; Ries, Maximilian (Mathematics and Mechanics of Solids, 2023)
The addition of nano-sized filler particles to polymers leads to significant improvements in their mechanical properties. These can be traced back to the matrix–filler interactions of the interphase, which can be analyzed using molecular dynamic simulations. Usually, research in this context studies the general number of entanglements or the radius of gyration. However, this publication presents a novel approach by investigating the radial distribution of entanglements in an effort to characterize the interphase. To this end, we employ a coarse-grained model for a generic polymer composite and study multiple systems with varying particle radius and matrix–filler adhesion. Furthermore, the highly customizable and computationally efficient nanocomposite system developed during this research serves as a foundation for the further characterization of polymer nanocomposites and their interphases.
CRIS-Team Scopus Importer:2023-12-15
Keywords: chain entanglement density; distribution functions; interphase; Molecular dynamics; polymer nanocomposite